AB1202 Visualization of remission of arthritis under tnf-inhibition in a patient with juvenile idiopathic arthritis using ICG-enhanced fluorescence optical imaging. (23rd January 2014) - Werner, S.G.; Langer, H.-E.; Backhaus, M.; Horneff, G.
Abstract : Background: Closed to medical history and clinical examination imaging tools are useful for valid detection of inflammation in patients with juvenile idiopathic arthritis (JIA). Prognosis is different in oligo- or polyarticular involvement and influences the therapeutic strategy. Ultrasonography and MRI are superior to clinical examination and other imaging modalities, but have practical limitations. Indocyaninegreen (ICG)-enhanced fluorescence optical imaging (FOI) is a novel imaging tool for visualization of inflammation in arthritis [1]. First experiences in children with an approved, commercial available FOI system were made (2). We want to report our first experiences in using FOI for monitoring of treatment response in JIA. Objectives: To analyze the treatment response under adalimumab in JIA with FOI. Methods: Clinical examination (CE), laboratory tests, grey scale ultrasound (GSUS) and FOI (Xiralite, mivenion GmbH, Berlin, Germany using ICG-Pulsion®, 0, 1mg/kg/KG i.v.) before (t0) and 4 months after starting Adalimumab (ADA, t1) of a 16 year old girl with polyarticular JIA and symptoms in wrists and finger joints (RF negative, ACPA negative, HLA-B27 negative, dd 12months, 4months therapy with NSAIDS, and 8months with MTX and Prednisone). Results: At t0 CE presents persistent poly-articular inflammation with aching swelling of the proximal interphalangeal joints (PIP) 2-4 in both hands, left knee and PIP 3 of the left foot. Residual morning stiffness of 10min existed under Prednisone therapy. No relevant reduction of disease activity under MTX was happened. GSUS showed an effusion in PIP joints. CE detected 7 tender and 9 swollen joints. FOI showed increased signal intensity in projection of the wrists, PIP-, and DIP- joints. A TNFa-inhibitor therapy was started with ADA 40mg s.c. every second week. Two months later, because of vomiting and nausea, the therapy with MTX was finished and monotherapy with ADA continued. At month 4 of treatment with ADA (t1) the patient was completely free of symptoms, and had no inflammatory activity in clinical examination (TJC and SJC each 0). FOI showed a normal finding. Conclusions: The increase of the therapeutic armamentarium in paediatric rheumatology permitted to define new treatment targets in JIA. Inactive disease or remission is achievable. The target is not easy to define. If the clinical evaluation of subclinical activity in inflammatory rheumatic disease is inferior to imaging modalities, a valid method for detection of residual subclinical inflammatory activity would be highly welcomed. With current knowledge, FOI seems to be an interesting option. The clinical decrease of symptoms correlates in this reported JIA patient with the decrease of pathological findings in FOI. A study (1) has shown it to be very sensitive, thus it could be an additional tool for therapy monitoring, perhaps even for assistance for the decision of adapting the therapy intensity. A structured evaluation of FOI for the scientific status in JIA is ongoing. References: Werner SG, Langer HE, Ohrndorf et al. Inflammation assessment in patients with arthritis using novel in vivo fluorescence optical imaging technology. Ann Rheum Dis Oct 2011, Epub ahead of print. Werner SG, Langer HE, Horneff G. Fluorescence optical imaging of juvenile arthritis. J rheumatol 2011; 38: 1447 Disclosure of Interest: S. Werner Grant/Research support from: Pfizer, H.-E. Langer Grant/Research support from: Pfizer, M. Backhaus Grant/Research support from: Pfizer, G. Horneff Grant/Research support from: Pfizer and Abbott